2010
DOI: 10.1186/1746-4269-6-14
|View full text |Cite
|
Sign up to set email alerts
|

The use of medicinal plants in the trans-himalayan arid zone of Mustang district, Nepal

Abstract: BackgroundThis study documents the use of medicinal plants from the Mustang district of the north-central part of Nepal. Traditional botanical medicine is the primary mode of healthcare for most of the population of this district and traditional Tibetan doctors (Amchi) serve as the local medical experts.MethodsField research was conducted in 27 communities of the Mustang district in Nepal from 2005-2007. We sampled 202 interviewees, using random and snowball sampling techniques. After obtaining prior informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
83
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 21 publications
16
83
1
1
Order By: Relevance
“…5). Similar results were also reported in other ethno-medicinal studies (Lulekal et al, 2008;Bhattarai et al, 2010;Rana et al, 2010) …”
Section: Routes Of Administrationsupporting
confidence: 80%
See 1 more Smart Citation
“…5). Similar results were also reported in other ethno-medicinal studies (Lulekal et al, 2008;Bhattarai et al, 2010;Rana et al, 2010) …”
Section: Routes Of Administrationsupporting
confidence: 80%
“…Roots of the plant were used for higher number of remedies (22) followed by the leaves (14) and seeds (10). Higher proportion of ethno-medicinal practices from root sources was also reported by Lulekal et al (2008), Bhattarai et al (2010), and Cheikhyoussef et al (2011).…”
Section: Plant Parts Usedmentioning
confidence: 86%
“…However, Bhattarai et al (2010) on their study in Mustang district of Nepal reported the use of the species as fence and medicine for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally managed agricultural productivity not only provides a major contribution to local consumption, but also substantially contributes to feeding the livestock in Manang and other parts of the ACAP region (Chaudhary et al, 2007). Animal husbandry is an integral part of the farming system; manure is an essential fertilizer (Aase et al, 2009) locally available plant species used to treat different ailments and diseases (Bhattarai et al, 2010 We also noticed local people in Shikha and Marpha are dependent on wild edible plant species and gather substantial amounts of wild plants to meet their daily nutritional needs.…”
Section: Implications Of Traditional Practices On Environmentmentioning
confidence: 99%